Active Citizenship Learning in Higher Education - Ingrid Geier (Forum Neue Medien in der Lehre Austria, 2018)
Citizenship participation has increasingly become a core concern for universities. The article will firstly present the task of a third mission. In addition, and as a comparison to the familiar concepts, service learning and civic engagement, the concept active citizenship learning, will be introduced. This is a higher education didactics concept in which academic learning and civic involvement complement one another. A change of perspective and a deeper awareness of democracy is being sought. Ideally, this can be achieved by becoming acquainted with and actively involved in, civil society.